Financial literacy in the Early Years of Primary School: children’s literature as a proposal for children to reflect on conscious consumption: - Silveira, Juliana Madruga da; Montoito, Rafael (Educação Matemática Debate, 2024)
Financial Literacy is understood as the ability to understand, analyze and apply financial concepts in everyday situations, not necessarily linked to money, but which cover topics such as conscious consumption, sustainability, the environment and other ways of being and relating to the world. Based on this concept, this paper, which is part of a dissertation developed as part of a professional master’s degree, aims to present a pedagogical practice carried out at the interface of Literature and Mathematics, designed to address Financial Literacy topics with students in the Early Years of Primary School. The dialogues established with the children raise questions about conscious consumption, sustainability and respect for the environment, topics that run counter to the attitudes encouraged by the consumer society.